Microeconomics: Behavioural Economics and Finance - Shogren, Jason F. (Journal of Economic Literature, 2013)
Jason F. Shogren of University of Wyoming reviews, “Behavioural Economics and Finance” by Michelle Baddeley. The Econlit abstract of this book begins: “Explores key concepts and insights from behavioral economics and its interdisciplinary approach to real-world decision making. Discusses foundations—psychology; foundations—neuroscience and neuroeconomics; learning; sociality and identity; heuristics and biases; prospects and regrets; personality, moods, and emotions; time and plans; bad habits; financial instability; and behavioral macroeconomics, happiness, and well-being. Baddeley is Fellow and Director of Studies (Economics) at Gonville and Caius College, Cambridge University.”